1985
DOI: 10.2151/jmsj1965.63.5_703
|View full text |Cite
|
Sign up to set email alerts
|

A Laboratory Investigation of the Structure of Multiple Vortices

Abstract: The structure of the multiple vortices formed in small scale atmospheric vortices is studied in a laboratory experiment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Several investigators have studied in laboratory experiments (Monji, 1985) and in theoretical experiments (Snow, 1978;Staley and Gall, 1979). Snow (1978) investigated the "inertial" st ability of vortex with an "internal shear layer"; the other hand, Staley and Gall (1979) also studied the barotropic instability and found the wave number of the order of 1 to 5 are significantly unstable.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have studied in laboratory experiments (Monji, 1985) and in theoretical experiments (Snow, 1978;Staley and Gall, 1979). Snow (1978) investigated the "inertial" st ability of vortex with an "internal shear layer"; the other hand, Staley and Gall (1979) also studied the barotropic instability and found the wave number of the order of 1 to 5 are significantly unstable.…”
Section: Discussionmentioning
confidence: 99%
“…For the laboratory simulators used by Church et al (1979), Monji (1985), Mishra et al (2008), Matsui and Tamura (2009) and Tari et al (2010) and the numerical simulators used by Rotunno (1977), Wilson and Rotunno (1986), and Ishihara et al (2011), the swirl ratio has historically been defined as the ratio of the angular …”
Section: Definitions Of the Swirl Ratiomentioning
confidence: 99%
“…Concurrent with the expansion of the core, the inner downdraft penetrates to the ground surface; a family of several secondary vortices rotating around the main vortex is evident. Church et al (1979) and Monji (1985) reported the vortex type as a function of the Reynolds number and the swirl ratio. It was concluded that the vortex type depends slightly on the Reynolds number; this dependency decreases for higher Reynolds numbers.…”
Section: Flow Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Tornado Vortex Chamber at Kyoto University (Monji, 1985) provided circulation by means of four fans operating in an annular region surrounding the inflow, but these fans produced unwanted turbulence within the simulator at all swirl ratios. Rothfusz (1986) provided circulation that could be varied as a function of height in a modified Ward simulator with a three-tier system of vanes.…”
Section: Article In Pressmentioning
confidence: 99%